Answer:
x = 7
General Formulas and Concepts:
Pre-Algebra
- Order of Operations: BPEMDAS
- Equality Properties
Explanation:
Step 1: Define equation
7x - 6 = 8 + 5x
Step 2: Solve for x
- Subtract 5x on both sides: 2x - 6 = 8
- Add 6 to both sides: 2x = 14
- Divide 2 on both sides: x = 7
Step 3: Check
Plug in x into the original equation to verify it's a solution.
- Substitute in x: 7(7) - 6 = 8 + 5(7)
- Multiply: 49 - 6 = 8 + 35
- Subtract/Add: 43 = 43
Here we see that 43 does indeed equal 43.
∴ x = 7 is a solution of the equation.